The ethics of parenthood - Richards, Norvin, 1943- (New York ; Oxford : Oxford University Press, 2010)
Norvin Richards explores the moral relationship between parents and children from slightly before the cradle to before the grave. Richards maintains that biological parents do have a right to raise their children, not as a property right but as an instance of our general right to continue whatever we have begun.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed Sept. 7, 2010).
Keywords: Parenting -- Moral and ethical aspects